Thymocyte‐derived BDNF influences T‐cell maturation at the DN3/DN4 transition stage. Issue 5 (19th February 2015) - Linker, Ralf A.; Lee, De‐Hyung; Flach, Anne‐Christine; Litke, Tanja; van den Brandt, Jens; Reichardt, Holger M.; Lingner, Thomas; Bommhardt, Ursula; Sendtner, Michael; Gold, Ralf; Flügel, Alexander; Lühder, Fred
<x xml:space="preserve">Abstract</x> Brain‐derived neurotrophic factor (BDNF) promotes neuronal survival, regeneration, and plasticity. Emerging evidence also indicates an essential role for BDNF outside the nervous system, for instance in immune cells. We therefore investigated the impact of BDNF on T cells using BDNF knockout (KO) mice and conditional KO mice lacking BDNF specifically in this lymphoid subset. In both settings, we observed diminished T‐cell cellularity in peripheral lymphoid organs and an increase in CD4+CD44+ memory T cells. Analysis of thymocyte development revealed diminished total thymocyte numbers, accompanied by a significant increase in CD4/CD8 double‐negative (DN) thymocytes due to a partial block in the transition from the DN3 to the DN4 stage. This was neither due to increased thymocyte apoptosis nor defects in the expression of the TCR‐β chain or the pre‐TCR. In contrast, pERK but not pAKT levels were diminished in DN3 BDNF‐deficient thymocytes. BDNF deficiency in T cells did not result in gross deficits in peripheral acute immune responses nor in changes of the homeostatic proliferation of peripheral T cells. Taken together, our data reveal a critical autocrine and/or paracrine role of T‐cell‐derived BDNF in thymocyte maturation involving ERK‐mediated TCR signaling pathways.